1994
DOI: 10.3758/bf03208892
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of face recognition and the other-race effect

Abstract: The other-race effect was examined in a series of experiments and simulations that looked at the relationships among observer ratings of typicality, familiarity, attractiveness, memorability, and the performance variables of d' and criterion. Experiment 1 replicated the other-race effect with our Caucasian and Japanese stimuli for both Caucasian and Asian observers. In Experiment 2, we collected ratings from Caucasian observers on the faces used in the recognition task. A Varimax-rotated principal components a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
176
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(190 citation statements)
references
References 23 publications
12
176
2
Order By: Relevance
“…With a single glance, we can extract abundant facial information about a person such as their gender, age, race, identity and expression. This highly efficient cognitive processing for faces seems to be correlated with our prior experience of face encountering, as clearly demonstrated by psychological studies such as own-race bias (e.g., O'Toole, Deffenbacher, Valentin, & Abdi, 1994). That is, in comparison with faces of people from our own race, processing less experienced faces from other races often results in frequent misidentification, poorer performance in recognition, memory and perceptual discrimination, and less accurate judgement of age and gender (Dehon & Brédart, 2001;Levin, 2000;Meissner & Brigham, 2001).…”
Section: Introductionmentioning
confidence: 70%
“…With a single glance, we can extract abundant facial information about a person such as their gender, age, race, identity and expression. This highly efficient cognitive processing for faces seems to be correlated with our prior experience of face encountering, as clearly demonstrated by psychological studies such as own-race bias (e.g., O'Toole, Deffenbacher, Valentin, & Abdi, 1994). That is, in comparison with faces of people from our own race, processing less experienced faces from other races often results in frequent misidentification, poorer performance in recognition, memory and perceptual discrimination, and less accurate judgement of age and gender (Dehon & Brédart, 2001;Levin, 2000;Meissner & Brigham, 2001).…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, better (more recognizable) averages are built from larger numbers of exposures. PCA has been proposed as a model of some aspects of human face processing (e.g., O'Toole et al, 1994;) and the advantage it shows when using an abstract representation appears to offer potential for understanding human face recognition. When one's task is to establish the identity of a face, superficial image cues such as contrast, illumination, lighting direction etc, must somehow be filtered out.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to perform a statistical analysis, such as PCA (see Box 1), on a set of face images, and to establish whether there are correspondences between the derived components and human performance. A number of studies have found such correlations [34][35][36] but it is often hard to give labels to the dimensions. PCA may offer a feel for the dimensionality of the space: e.g.…”
Section: Distinctiveness and Face Spacementioning
confidence: 99%